Antibacterial Activity of Polygonum pulchrum Blume Ethanol Extract on Staphylococcus aureus and Escherichia coli - Sadino, Asman; Sahidin, Idin; Wahyuni, Wahyuni (Pharmacology and Clinical Pharmacy Research, 2018)
The emergence of resistant bacteria strain has become a global health concern. It encourages the exploration of potential antibacterial agents, particularly from natural sources. The aim of this study was to investigate the antibacterial activity of ethanol extract of root, stems, leaves, and flowers of Polygonum pulchrum Blume against Staphylococcus aureus and Escherichia coli, through disc diffusion method using cup-plate method. Inhibition zone against S. aureus from roots, stems, leaves, and flowers ethanol extract were 3.5 mm, 2.5 mm, 2.25 mm, and 2.62 mm, respectively, while the inhibition zone against E. coli were 2.25 mm, 2.12 mm, 1.62 mm, and 1.75 mm, respectively. In conclusion, ethanol extract of root, stem, leaves, and flower of P. pulchrum Bl possessed weak antibacterial activity against S. aureus and E. coli.Keywords: P. pulchrum Bl, antibacterial, E. coli, S. aureus, cup-plate technique